Critical Humanism and Problems of Change - Rodriguez, Arturo; Magill, Kevin R. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Guest editors’ introduction to special section, Investigating Education, Class Antagonisms and Solidarity: Toward Critical Humanist Democratic Societies. This collection details how critical educators contend with alienating conditions as students and teachers investigate social issues, direct knowledge, their exchanges, and personal agency toward democratic participation to secure their everyday needs, human freedom, and dignity.